Investigating metformin’s mechanism of action for weight loss in obese people living with HIV treated with dolutegravir-based antiretroviral therapy - Karani, Alvin Wekesa (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.